2017
DOI: 10.1007/s00726-017-2424-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary l-tryptophan supplementation on intestinal response to chronic unpredictable stress in broilers

Abstract: Stress has been recognized as a critical risk factor for gastrointestinal diseases in both humans and animals. However, nutritional strategies to attenuate stress-induced intestinal barrier function and underlying mechanisms remain largely unknown. This study tested the hypothesis that L-tryptophan enhanced intestinal barrier function by regulating mucosal serotonin metabolism in chronic unpredictable stress-exposed broilers. One-day-old male broilers (Arbor Acres) were fed a basal diet supplemented with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
1
31
1
Order By: Relevance
“…Whether peripheral serotonin, particularly plasma serotonin, affects glucose and lipid metabolism as well as FCR in broiler chickens is unknown. A recent study showed that supplementation of broiler chicken diet with tryptophan may improve FCR under chronic and unpredictable stress, probably owing to serotonergic metabolism (Yue et al, 2017). Therefore, the metabolic role of peripheral serotonin has been identified in broilers in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…Whether peripheral serotonin, particularly plasma serotonin, affects glucose and lipid metabolism as well as FCR in broiler chickens is unknown. A recent study showed that supplementation of broiler chicken diet with tryptophan may improve FCR under chronic and unpredictable stress, probably owing to serotonergic metabolism (Yue et al, 2017). Therefore, the metabolic role of peripheral serotonin has been identified in broilers in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…The supplementation of Trp inhibits Th1 differentiation in vivo [ 61 ]. And L-Trp supplementation decreases the destruction of intestinal barrier triggered by stress via modulating 5-HT metabolism in broilers [ 62 ]. Collectively, EAAs mainly exert anti-inflammatory roles by NF- κ B, CaSR, MAPK, and mTOR signaling pathway to restrain the expressions of proinflammatory cytokines.…”
Section: Amino Acids and Intestinal Inflammationmentioning
confidence: 99%
“…Whereas oxidative stress puts harmful effects on membran fludity. The 5-HT has beneficial effects on the enzymatic and non-enzymatic anti-oxidant capacity (Dong, Azzam, Rao, Yu, & Zou, 2012;Yue, Guo, & Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%